Stimulation of innate immunity in newborn kids against Cryptosporidium parvum infection-challenge by intranasal/per-oral administration of liposomal formulation of N-L18-norAbu-GMDP adjuvant - Turánek, J; Kasná, A; Koudela, B; Ledvina, M; Miller, A D (Parasitology, 2005)
The effects of a liposomal preparation of lipophilic immunomodulator beta-D-GlcNstearoyl-(1-4)-norMurNAc-L-Abu-D-isoGln (N-L18-norAbu-GMDP) were investigated on resistance to Cryptosporidium parvum infection in neonatal kids. The liposomal preparation was administered subcutaneously or intranasally/orally (i.n./p.o.) twice at doses of 100 microg, 200 microg, or 1000 microg per kid pre-infection challenge. The treatment schemes were (i) 72 and 24 h pre-infection challenge, (ii) 24 h pre-infection challenge and 24 h post-infection challenge (oral inoculation with 1 x 10(7) oocysts of C. parvum in 5 ml of PBS). Administration of liposomal N-L18-norAbu-GMDP by i.n./p.o. route at the cumulative dose of 2000 microg per kid 72 and 24 h pre-infection challenge, lead to substantially increased clearance of coccidian parasites from various parts of the intestine. On the basis of histological examination, the distribution of cryptosporidia in the intestine and the severity of the infection, treated kids were classified on day 5 as having a strong reduction in infection in comparison to the control group (P < 0.05). No cryptosporidia were found on the mucosal surface of treated kids by day 10, while the intestines of the control kids were still infected. All doses and routes of administration were judged effective with respect to suppression of cryptosporidia infections.
Keywords: mužské pohlaví; kryptosporidióza; jejunum; Male; novorozená zvířata; Administration, Oral; Administration, Intranasal; Female; Cryptosporidiosis; Protozoan Proteins; aplikace intranazální; Goats; Time Factors; Cryptosporidium parvum; ženské pohlaví; vztah mezi dávkou a účinkem léčiva; Animals, Newborn; nemoci koz; kozy; Animals; Dose-Response Relationship, Drug; Jejunum; zvířata; liposomy; aplikace orální; adjuvancia imunologická; Goat Diseases; Liposomes; časové faktory; protozoální proteiny; průjem; Diarrhea; Adjuvants, Immunologic